Effect of Auditor Specialization, Auditor Characteristics, Board Independence on Audit Quality through intellectual capital : Study on service companies - Syamsu Rijal; Asri Ady Bakri; Arjang (Eastasouth Institute, 2023)
This study aims to examine the effect of auditor specialization, auditor characteristics, and board independence on audit quality through intellectual capital in service companies in West Java. The research was conducted using a quantitative approach with a sample of 384 service companies in West Java. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results of this study showed that auditor specialization, auditor experience, and board independence had a positive and significant effect on audit quality. Meanwhile, intellectual capital has a significant mediating effect on the relationship between auditor specialization, auditor experience, and board independence on audit quality. The findings of this study provide important insights into the factors that contribute to the enhancement of audit quality in service companies. This study suggests that service companies in West Java should consider hiring specialized auditors, experienced auditors, and independent boards to improve audit quality. Additionally, companies should also focus on the development of intellectual capital, which plays an important role in enhancing audit quality.